Analisis Deskriptif Kemampuan Menulis Teks Proposal Melalui Pendekatan Project Based Learning pada Siswa Kelas XI PSPT Sekolah Menengah Kejuruan Muhammadiyah Bojong - Oktaviani, Diah; Hardiyanto, Fahrudin Eko (Jurnal Bahastra, 2025)
Project-Based Learning (PBL) is an instructional strategy that enables students to apply their knowledge and skills in real-world projects with meaningful impact. Enhancing proposal writing skills through PBL equips students with creativity, problem-solving abilities, and effective communication, which are essential for meeting industry demands. This study aims to explore the implementation of the PBL approach in improving students' proposal writing skills and examines changes in their attitudes toward writing proposals after applying this method in Class XI PSPT at SMK Muhammadiyah Bojong. This research employs a descriptive qualitative approach to analyze students' learning experiences and outcomes. The findings indicate that PBL significantly enhances students' ability to write structured and coherent proposals, increases motivation, fosters active engagement in the learning process, and develops collaborative and social competencies. These results suggest that integrating PBL into proposal writing instruction can create a more interactive and meaningful learning experience while preparing students for real-world professional challenges.